(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This scientific article analyzes the existence, nature, relationship between reading and the book, as well as the ontological and epistemological characteristics of reading and the book in terms of their functional properties. In addition, the complex cognitive process of understanding the text as a means of language, communication, obtaining information, and exchanging ideas is emphasized.